(untitled) (Innovative professional education, 2025)
Integration processes in the reform of general secondary education in the European Union are aimed at harmonising curricula, developing inclusive and digital learning, and supporting the mobility of learners and teachers. EU education policies play an important role in improving the quality of education and ensuring equal access to education. At the same time, the implementation of reforms faces challenges due to national peculiarities and financial differences between EU member states.